DAYA AKUMULASI LOGAM BERAT TEMBAGA (Cu) PADA AKAR DAN DAUN Avicennia marina (Forsk.) BERDASARKAN FASE PERTUMBUHAN YANG BERBEDA DI PANTAI MANGKANG SEMARANG - Ahmad Fadhli Jundana; Endah Dwi Hastuti; Rini Budi Hastuti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Distribution of heavy metals in coastal areas need to know as an early indication of pollution. One type of metal that was widely used in household and industrial activity is copper (Cu). Some pollutants were wasted on the ground will have accumulated in coastal areas, including in the mangrove ecosystem. The research aims to determine the accumulated rate Cu in roots and leaves of Avicennia marina by different growth phases. It was conducted in mangrove ecosystems Mangkang, Semarang. The research design was factorial completely randomized design 2 x 3, the first factor were organs (roots and leaves) and the second factor were phase (Seedling, Sapling and Trees) with twice of sampling in a 30-day period, the data were analyzed by Analyzed of Variates (ANOVA). Parameter of the research were Cu metal content in the roots and leaves of mangrove, as well as water and sediment. The results showed that the levels of Cu in sediments and aquatic environments of Avicennia marina rangely 2.989-7.026 mg/kg and 0.186-1.676 mg/l, there was an interaction between the growth phase and organs Avicennia marina in accumulating Cu with a probability of 0.006 (< 0.05), the highest interaction was the tree phase and root organ section (0.126) and the lowest was the seedling phase and leaf organ (0.020). The highest of Biological Concentration Factor (BCF) value was tree phase and root organ (92.9- 46.2) and the lowest was the seedling phase and leaf organ (17.2-14.7). The highest of Distribution Coefficient (DC) value was found in seedling phase environment (726.3-1887.7) and the lowest was found in sapling phase environment (493.2-603.4).Key Words : Accumulation, Avicennia marina (forks.), Heavy Metal Cu, Biological Concentration Factor, Distribution Coefficient